2013
DOI: 10.1155/2013/867575
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Gait Impairment Using an Instrumented Treadmill in People with Multiple Sclerosis

Abstract: Background and Objective. Treadmill gait analysis has been proposed as an attractive alternative for overground walking measuring systems. The purpose of this study was twofold: first to determine spatiotemporal parameters of treadmill gait in patients with multiple sclerosis (MS) and second to examine whether these parameters are associated with specific functional impairments in this cohort. Method. Eighty-seven relapsing-remitting patients diagnosed with MS, 50 women and 37 men, aged 40.9 ± 11.9 with an exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 26 publications
4
36
0
Order By: Relevance
“…Correlation between the symmetry gait parameter to the EDSS score was 0.241 (P b 0.001) and 0.147 (P = 0.007) with the cerebellar function level. The current study's correlation results are similar to those presented in our previous report of 87 PwMS [17].…”
Section: Spearman's Rho Correlation Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…Correlation between the symmetry gait parameter to the EDSS score was 0.241 (P b 0.001) and 0.147 (P = 0.007) with the cerebellar function level. The current study's correlation results are similar to those presented in our previous report of 87 PwMS [17].…”
Section: Spearman's Rho Correlation Analysissupporting
confidence: 92%
“…An advantage of this device is that it measures walking over relatively long distances, possibly reflecting the fatigue component common in PwMS. In our previous report, we demonstrated that spatiotemporal gait parameters, collected by the instrumented treadmill, serve as valid markers of neurological impairment in the MS population [17].…”
Section: Introductionmentioning
confidence: 98%
“…Recently, the instrumented treadmill has been found to be an appropriate tool for assessing ambulation capabilities in people with MS. Furthermore, spatiotemporal gait parameters collected by this device during walking seem to be valid markers of neurological impairment in the MS population [30].…”
Section: Methodsmentioning
confidence: 98%
“…Nowadays, the majority of researchers who adopts the plantar pressure to analyze the data are using electronic sensor based systems. These sensors can be in different configurations such as; mat [10][11][12], in-sole [13,14] and treadmill [15,16]. Conventionally however, these sensors lack the required resolution to measure or predict the pressure of small regions, such as the toes.…”
Section: Introductionmentioning
confidence: 99%